Exploring the potential value of alternating Philosophy with Picture Books (PB) with the Integrated Approach to Literacy Instruction (IATLI) to support two boys with dyslexia. - Harper, Helen (My University, 2014)
This study explored the potential value of alternating Philosophy with Picture Books (PB) within the Integrated Approach to Literacy Instruction (IATLI), to support two boys with dyslexia. PB was chosen in this explorative study because of its use of visual instruction, which a child with dyslexia is likely to respond more favourably to, because visual modes of learning is more complimentary to such learners. PB originates from the approach Philosophy with Children (P4C) that supports a pedagogy involving communicative virtues and collaborative thinking. Such attributes are likely to add value to an intervention as it may lead to the development of meta-cognitive strategies, which could both support and motivate their learning. The Integrated Approach to Literacy Instruction (IATLI) was also chosen in this explorative study because research suggests that children with dyslexia struggle with the acquisition of phonological awareness. One of the aims of the IATLI is to develop such a weakness. This study explores in particular how alternating the IALTI and PB could possibly add value in supporting two boys with dyslexia. The responses of both boys to the two approaches, in-depth interviews with both boys’ English teachers, and developmental diaries kept by the English teachers, the researcher, as well as the participants was analysed utilising thematic coding. In addition, pre and posttesting was administered and added to the triangulation of this study. The main findings indicated that alternating the IATLI and PB was valuable for these two boys and led to some improvement, relating to their personal development, positive attitude to engagement in remedial therapy, improved self esteem and areas of literacy improvement. It did not however result in significant improvement, as the boys did not transfer the skills taught in remedial therapy to the classroom, nor was significant improvement noticed by their English teachers.
Keywords: Dyslexia; Remedial therapy; IATLI; PB